Preparation of mesoporous hollow CMPs microspheres based on kinetic quantum sieving effect and its application in radioactive element adsorption

By designing mesoporous hollow CMPs microspheres based on the kinetic quantum sieve effect, the problems of poor selectivity and low adsorption efficiency of existing adsorption materials for radioactive I/Cs elements are solved, and efficient and stable iodine/cesium adsorption effect is achieved.

CN118558303BActive Publication Date: 2025-02-14LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410765235.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2025-02-14
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

The existing adsorbent materials have poor selectivity for radioactive I/Cs elements and have low adsorption efficiency. The iodine ions adsorbed in silver-based materials and bismuth-based materials are prone to fall off, which are harmful to the environment.

Method used

By designing and synthesizing conjugated microporous polymer (CMPs) microspheres with mesoporous hollow structures based on kinetic quantum sieve effect (KQS), the pore size structure and chemical composition are regulated to improve the adsorption performance of I/Cs elements. .

Benefits of technology

Mesoporous hollow CMPs microspheres with high adsorption, sensitive recognition, strong affinity and good stability were prepared under mild conditions, which significantly improved the adsorption efficiency and selectivity of radioactive I/Cs elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a method for constructing a CMPs adsorption material with a special hollow mesoporous structure based on the kinetic quantum sieving (KQS) effect. According to the size of the target molecule (iodine / cesium), the type of building block unit, the molecular chain length and the unit ratio of the skeleton structure are cleverly designed and regulated. 1,3,5-triethynylbenzene and 2,6-dibromonaphthalene or 2,7-dibromonaphthalene are used as monomers, and the Sonogashhara-Hagihara cross-coupling condensation reaction is adopted to synthesize a CMPs adsorption material with precise pore size requirements, so as to meet the efficient selective adsorption of the adsorption material to the target molecule. Based on the special hollow structure of the synthesized CMPs material, the problem of low diffusion rate caused by low temperature and microporous structure in I / Cs ion transfer can be effectively solved; the prepared CMPs-1 with a hollow mesoporous structure showed an iodide ion absorption rate of up to 16.93 mg g in 6 hours in an extreme low-temperature static adsorption experiment at 10°C. ‑1 The adsorption capacity of iodine ions reached 26.32 mg g at 30 °C. ‑1 . This is mainly attributed to the matching mesoporous structure (3-8 nm) of the synthesized CMPs material, and the three-dimensional network can provide sufficient space to accelerate the diffusion rate of reactants and intermediates, exposing more active sites. The synthetic strategy provided by the present invention can provide inspiration for the design and construction of porous functionalized adsorption materials for efficient adsorption / separation of specific targets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmentally friendly adsorption materials, and specifically relates to a method for preparing mesoporous hollow CMPs microspheres based on kinetic quantum sieving effect (KQS), and also relates to the application of the mesoporous hollow CMPs microspheres in the efficient adsorption of radioactive elements. Background Art

[0002] Although nuclear energy meets the energy needs of human society in its development, it inevitably brings about the problem of nuclear waste disposal. According to research, the radioactive emissions with high nuclear waste content mainly include 129 I. 131 I and 137 Cs. Among them, iodine ( 129 I) is a fission product of plutonium-239 and uranium-235. It is volatile and radioactive, with a radioactive half-life of up to 1.57×10 7 It is very easy to volatilize into the air, causing great damage to the ecological environment. In addition, radioactive iodine can enter the human body through food and water, which will not only damage the metabolic system, but also radiate in the human body and cause diseases such as thyroid cancer, breast cancer and leukemia. Therefore, the effective capture and storage of radioactive iodine is crucial to maintaining human health and achieving sustainable development of nuclear energy and the environment.

[0003] At present, a variety of methods have been developed for the treatment of radioactive elements, such as adsorption, membrane separation, ion exchange and chemical precipitation. Among them, the adsorption method has the advantages of high efficiency, no pollution, simple operation and wide source of adsorption materials, and is considered to be the most promising method for removing radioactive elements. Silver-based materials, bismuth-based materials, metal organic frameworks (MOFs), covalent organic frameworks (COFs), activated carbon and zeolite are widely used as adsorption materials. For example: Based on bayberry tannin and nanosilver, a multilayer active interface material based on collagen fibers (Ag-0@BT-nCF) was constructed. The second layer of iodine-active nanosilver particles was constructed through the chelation of silver with the carboxyl group of collagen and the hydroxyl group of bayberry tannin; the iodine capture results showed that Ag-0@BT-nCF showed higher iodine adsorption performance (1704 mg g) than other adsorbents. -1 ) (Appl. Surf. Sci. 2022, 569, 153585). Among silver-based materials, silver-based zeolite is a typical radioactive iodine adsorbent. For example, natural zeolite is modified with silver by different methods to prepare Ag2O and Ag(0) nanocomposites. The experimental results show that natural zeolite has no affinity for iodide, while silver-based zeolite exhibits significant iodine adsorption performance of 132 mg g -1(Nanomaterials, 2020, 10, 6, 1156). In addition, Bi-mna is a special type of bismuth metal-organic framework (MOF) for capturing and processing iodine. A hydrophobic bismuth-based chrysotile membrane modified with the silane coupling agent KH570 has a high affinity for iodine due to its abundant bismuth-loaded reaction sites; when water vapor is present during the iodine adsorption process, the hydrophobic surface imparted by KH570 acts as a "protective layer", and the prepared membrane has a maximum iodine capture efficiency of 483.37 mg g in air. -1 The iodine capture rate at 75% relative humidity can reach up to 443.04 mg g -1 , compared with the hydrophobic membrane without KH570 modification, the adsorption capacity of the hydrophobic membrane for iodine under humid conditions increased by about 54% (Sep. Purif. Technol. 2022, 302, 123374). In recent years, metal organic frameworks (MOFs), covalent organic frameworks (COFs), and porous activated carbons, as a fascinating porous material with structural diversity and chemical stability, have shown promising potential applications in gas capture and storage and adsorption. For example: fluorinated groups were introduced into MOFs, and two different strategies, ligand exchange and direct synthesis, were used to construct fluorinated zirconium-based PCN-222 and UiO-66, respectively; when interacting with iodine guests, both fluorinated MOFs showed enhanced structural stability, among which UiO-66-F showed 0.93gg -1 The iodine adsorption capacity of the anionic COF TpPaSO was improved by the ionic liquid method using aminotriazole cations, and the iodine adsorption kinetics (K-80%) of the ionic liquid-modified COF TpPaSO4 was five times higher than that of the original COF (Small, 2023, 19, 39, 1143). Alternatively, a high-surface-area nanoporous nitrogen-rich covalent organic framework (TTA-DMTP-COF) was synthesized for the adsorption of iodine (I-2) and methyl iodide (CH3I); adsorption experiments showed that the maximum adsorption capacity of TTA-DMTP-COF for I2 was as high as 2.59 gg -1(ACS Appl. Nano Mater. 2023, 6, 19, 18177). In addition, pretreatment, heat treatment and deep treatment techniques were used to synthesize biomass-derived porous carbon (K-RPC) with uniform wormhole-like micropores or nanopores and high specific surface area; the results showed that K-RPC exhibited extraordinary iodine capture performance, and its capacity exceeded that of most bio-based adsorbents (Sep. Purif. Technol. 2024, 347, 127613). In addition, the cationic dimethylammonium group in the acid-stabilized Zr(OBA)MOF is charge balanced with the anionic Zr(OBA)nn-, which is very effective for the removal of Cs + Effective, in 4 M HNO3 environment, pH 4 for Cs + The maximum adsorption capacity can reach 432.91 mg g -1 ; In the simulated seawater experiment, Zr(OBA)MOF has a strong affinity for Cs + The maximum adsorption capacity can reach 253.77 mg g -1 (Sep. Purif. Technol. 2024, 335, 126052). In the above research, many materials for adsorbing iodine ions / cesium ions have been developed, and their performance is relatively excellent. However, the iodine ions adsorbed in silver-based materials and bismuth-based materials are easy to fall off, and the silver ions themselves are harmful to the environment. Although metal organic frameworks (MOFs) and covalent organic frameworks (COFs) have made some achievements in the adsorption of iodine and cesium, there are still few reports on MOFs and COFs adsorption materials with high adsorption capacity, high stability and high selectivity; and most mesoporous MOFs and COFs are synthesized under high temperature, acid and organic solvent conditions, and their synthetic complexity and stability limit their practical application. In addition, porous materials such as activated carbon and zeolite have low removal efficiency and are difficult to regenerate; their pore size is difficult to adjust to match the target molecule. Therefore, it is crucial to construct an adsorption material that can regulate the pore size under mild conditions and has high adsorption, sensitive recognition, strong affinity and good stability.

[0004] Conjugated microporous polymers (CMPs) are porous polymer materials with conjugated structures, which are mainly formed by chemical bonds between aromatic compounds. With the characteristics of high specific surface area, highly adjustable pore performance and controllable morphology, CMPs have been widely used in adsorption, catalysis and separation since they were reported in 2007. Based on the above analysis, the present invention attempts to synthesize multilayer hollow CMPs microspheres with pore size matching, high adsorption, dynamic recognition and high selectivity through reasonable molecular design with aromatic compound building blocks of different spatial structures and chemical compositions for efficient iodine / cesium adsorption. CMPs have intrinsic advantages for the adsorption materials designed by the present invention with the characteristics of pore size matching, high adsorption, dynamic recognition and high selectivity. First, CMPs can accurately control the pore structure by regulating the type of building blocks, molecular chain length, unit ratio and synthesis conditions of its skeleton structure to meet the pore size requirements of the kinetic quantum sieving effect (KQS) adsorption material. Secondly, by changing the chemical composition of the building block units at the molecular level or / and introducing functional sites with strong binding force to I / Cs molecules or / and introducing groups with recognition of I / Cs molecules, the intrinsic structure of CMPs can be precisely regulated to meet the dynamic recognition, high affinity and high adsorption of the material, and further improve the selectivity of CMPs adsorption of I / Cs. The present invention is the first to construct a mesoporous hollow CMPs microsphere with high adsorption, sensitive recognition, strong affinity and good stability based on the kinetic quantum sieving effect under mild conditions, and is used for the study of efficient adsorption of radioactive I / Cs elements. Summary of the invention

[0005] In order to solve the shortcomings of the prior art that the adsorption materials have poor selectivity for radioactive I / Cs elements and low adsorption efficiency, the purpose of the present invention is to provide a method for preparing mesoporous hollow CMPs microspheres with high adsorption, sensitive recognition, strong affinity and good stability based on the kinetic quantum sieving effect under mild conditions.

[0006] Another object of the present invention is to provide the application of the mesoporous hollow CMPs microspheres prepared by the above method in the efficient adsorption of radioactive I / Cs elements. CMPs can form a pore structure (3-8 nm) that matches the target molecule without sacrificing its structural stability, so that CMPs can efficiently adsorb I / Cs elements. The special hollow structure of CMPs promotes the transfer and diffusion of I / Cs ions in the pores of CMPs.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing mesoporous hollow CMPs microspheres based on kinetic quantum sieving effect comprises the following steps:

[0009] 1,3,5-triethynylbenzene and bromo compounds are used as monomers, CuI and Pd are used as catalysts, added to a mixed solution of triethylamine and toluene, reacted at 60-90 °C in a nitrogen atmosphere in the dark for 40-50 h, cooled naturally after the reaction, washed, extracted with methanol solution, and then dried to obtain mesoporous hollow CMPs microspheres; the bromo compound is 2,6-dibromonaphthalene or 2,7-dibromonaphthalene. Synthesis route as follows Figure 1 (a).

[0010] The molar ratio of 1,3,5-triethynylbenzene to the brominated compound is 1:0.5-1:2. The mass ratio of 1,3,5-triethynylbenzene to CuI is 1:5-1:30; The mass ratio of CuI to Pd is 1:1-4:1. The volume ratio of triethylamine and toluene mixed solution is 1:0.5-1:2. The drying temperature is 60-90 °C and the drying time is 10-15 h.

[0011] The method mentioned above prepares a mesoporous hollow CMPs microsphere with high adsorption, sensitive recognition, strong affinity and good stability.

[0012] The application of the mesoporous hollow CMPs microspheres of the present invention in the efficient adsorption of radioactive I / Cs is specifically as follows:

[0013] The mesoporous hollow CMPs microspheres were added to a solution containing radioactive elements iodine or cesium and adsorbed at 10-50 °C for 2-12 hours. The concentration of iodine or cesium in the solution containing radioactive elements was 0.02-0.1 mg mL -1 .

[0014] The mechanism of the present invention is:

[0015] Since the design of the present invention is based on the kinetic quantum sieving (KQS) effect, the type of building block units, molecular chain length and unit ratio of the skeleton structure are cleverly designed and regulated according to the size of the target molecule (iodine / cesium), and the Sonogashhara-Hagihara cross-coupling condensation reaction is used to synthesize CMPs adsorption materials with precise pore size requirements to meet the efficient and selective adsorption of the adsorption materials to the target molecules. Secondly, the π-π conjugation between molecules in the CMPs synthesis process is used to construct CMPs microspheres with a special hollow structure. The hollow structure is not only conducive to the diffusion of target molecules, but also can effectively solve the problem of low diffusion rate caused by low temperature and microporous structure of materials during the adsorption process; in addition, the spherical hollow structure can effectively amplify the diffusion rate and promote the recognition of target molecules by the material. Secondly, the hollow CMPs microspheres synthesized by the designed symmetrically substituted structure (2,6-dibromonaphthalene) have a mesoporosity of 94%, and their three-dimensional network structure can not only provide sufficient space to accelerate the diffusion rate of reactants and intermediates, but also expose more active sites, which can provide more binding sites for adsorbed ions, enhance the adsorption performance, and improve the adsorption efficiency of iodine / cesium ions.

[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0017] 1. The present invention is the first to precisely control the pore structure of the CMPs adsorbent material based on the kinetic quantum sieving (KQS) effect according to the size of the target molecule (iodine / cesium) by cleverly designing the molecular chain length, type and unit ratio of the constructed monomers, so that 1,3,5-triethynylbenzene and 2,6-dibromonaphthalene or 2,7-dibromonaphthalene undergo Sonogashhara-Hagihara cross reaction to construct a CMPs adsorbent material with a pore size structure and spatial structure matching the size of the target molecule (iodine / cesium).

[0018] 2. The CMPs adsorption material prepared by the present invention can construct a CMPs adsorption material with a mesoporous structure by using the Sonogashhara-Hagihara cross reaction; the present invention can construct CMPs microspheres with a special hollow structure through a simple strategy.

[0019] 3. The hollow CMPs adsorption material prepared by the present invention can effectively solve the problem of low diffusion rate caused by low temperature and microporous structure in iodine / cesium ion transfer due to its special hollow structure and π-conjugated system. In particular, in the extreme low temperature static adsorption experiment at 10°C, CMPs-1 showed an iodine ion absorption rate of up to 16.93 mg g within 6 hours. -1 adsorption capacity.

[0020] 4. The hollow CMPs adsorption material prepared by the present invention can precisely control the pore structure of the CMPs adsorption material according to the size of the target molecule (iodine / cesium), increase the precise mesoporous structure (especially significantly increase at 3-8 nm), accelerate the diffusion rate of reactants and intermediates, and provide sufficient adsorption sites for the exposure of active sites. The constructed CMPs-1 exhibits excellent heat resistance and has a higher iodine adsorption capacity of 26.32 mg g at 30 °C compared with 10 °C. -1 (1.6 times). The maximum adsorption capacity of CMPs-2 for cesium ions at 600 ppm is 4.75 mg g -1 , the adsorption equilibrium time is only 10 minutes.

[0021] 5. The hollow CMPs adsorption material prepared by the present invention has excellent alkali resistance due to the construction of the π-π conjugated system and the three-dimensional network, and maintains an effective iodide ion adsorption capacity (16.93-5.92 mg g -1 ). In addition, the adsorbent material prepared by the present invention exhibits excellent cyclic stability. Therefore, the synthesis strategy provided by the present invention can provide inspiration for the design and construction of porous functionalized adsorbent materials for efficient adsorption / separation of specific targets. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) Synthesis route and molecular structure of Examples 1-2 of the present invention; (b) Schematic diagram of process preparation of Examples 1-2 and Comparative Example 2; (c) Simulated adsorption diagram of CMPs adsorption material for iodine / cesium ions.

[0023] Figure 2 (a) is a photograph of Example 1 of the present invention in solution and (b) a SEM image; (c) is a photograph of Example 2 of the present invention in solution and (d) a SEM image; (e), (f) are TEM images of Example 1 and Example 2 of the present invention; (g), (h) are TEM-EDS mappings of Example 1 and Example 2 of the present invention; (i) a photograph of Comparative Example 2 in solution and (j) a SEM image; (k) a photograph of Comparative Example 1 in solution and (l) a SEM image.

[0024] Figure 3(a) is the XRD spectrum of Example 1-2 of the present invention and Comparative Example 1-2 and (b) FT-IR curve; (c) is the N2 adsorption / desorption curve of Example 1-2 of the present invention; (d) is the BJH pore size distribution curve of Example 1-2 of the present invention; (e) is the N2 adsorption / desorption curve of Comparative Example 1-2; (f) is the BJH pore size distribution curve of Comparative Example 1-2; (g) is the XPS measurement spectrum of Example 1-2 of the present invention and Comparative Example 1-2; (h), (i) are the C1s spectra of Example 1-2 of the present invention; (j), (k) are the Br3d spectra of Example 1-2 of the present invention; (l) is the thermogravimetric analysis curve of Example 1-2 of the present invention and Comparative Example 1-2.

[0025] Figure 4 (a) is the adsorption diagram of I / Cs ions of Examples 1-2 and Comparative Examples 1-2 of the present invention; (b) is the UV-VIS adsorption diagram of Example 1 under static conditions for 30 minutes, and the standard curve of iodide concentration and absorbance; (c), (d), (e) and (f) are the absorption curves of different initial concentrations adsorbed at different times of Examples 1-2 and Comparative Examples 1-2; (g) and (h) are the adsorption curves of Examples 1-2 at different initial cesium ion concentrations.

[0026] Figure 5 (a), (b), (c) and (d) are the pseudo-first-order kinetic fitting curves and pseudo-second-order kinetic fitting lines of Examples 1-2 of the present invention and Comparative Examples 1-2, respectively.

[0027] Figure 6 (a), (b), (c) and (d) are the intra-particle diffusion fitting curves of Examples 1-2 of the present invention and Comparative Examples 1-2, respectively; (e) the Langmuir isotherm model adsorption fitting curve of Example 1 and (f) the Freundlich isotherm model adsorption fitting method; (g) the Langmuir isotherm model adsorption fitting curve of Example 2 and (h) the Freundlich isotherm model adsorption fitting method; (i) the Langmuir isotherm model adsorption fitting curve of Comparative Example 2 and (j) the Freundlich isotherm model adsorption fitting method; (k) the Langmuir isotherm model adsorption fitting curve of Comparative Example 1 and (1) the Freundlich isotherm model adsorption fitting method.

[0028] Figure 7 The diagram is a diagram of the iodine cesium ion adsorption mechanism of Examples 1-2 of the present invention and Comparative Examples 1-2.

[0029] Figure 8(a) Adsorption capacity of Example 1 under alkaline conditions; (b) Adsorption capacity of Example 2 under acidic conditions; (c) and (d) are high temperature resistance test and cycle stability test of Examples 1-2 of the present invention and Comparative Examples 1-2, respectively. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0031] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0032] Comparative Example 1

[0033] Add 7.5 mmol urea and 0.015 mol Cu(NO)2·3H2O to 60 mL 0.5 mL - 1 sucrose solution, stirred for 30 min, and stored in a vacuum oven at 180 °C for 12 h. The crude product was washed with deionized water and anhydrous ethanol and dried at 80 °C for 12 h. The residue was then heated in a tube furnace at 3 °C min - CuOHS was obtained by heating at a heating rate of 1 to 500°C for 3 h, and the sample was ground and stored at room temperature for later use.

[0034] Comparative Example 2

[0035] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 3,5-dibromo-2-pyridinamine (1 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-3), and the dried sample was stored at room temperature for later use.

[0036] Example 1

[0037] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 2,6-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-1), and the dried sample was stored at room temperature for later use.

[0038] Example 2

[0039] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 2,7-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-2), and the dried sample was stored at room temperature for later use.

[0040] Example 3

[0041] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (2 mmol) and 2,6-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-4), and the dried sample was stored at room temperature for later use.

[0042] Example 4

[0043] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 2,6-dibromonaphthalene (2 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-5), and the dried sample was stored at room temperature for later use.

[0044] Example 5

[0045] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 2,6-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (200 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-6), and the dried sample was stored at room temperature for later use.

[0046] Example 6

[0047] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (2 mmol) and 2,7-dibromonaphthalene (4 mmol) were added to the glass tube as monomers, CuI (100 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-7), and the dried sample was stored at room temperature for later use.

[0048] Example 7

[0049] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (1 mmol) and 2,7-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (200 mg) and Pd (0) (100 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-8), and the dried sample was stored at room temperature for later use.

[0050] Example 8

[0051] Toluene (7.5 mL) and triethylamine (7.5 ml) were added to a 50 mL flat-bottom glass tube and magnetically stirred for 30 min under a nitrogen atmosphere. Then, 1,3,5-triethynylbenzene (2 mmol) and 2,7-dibromonaphthalene (1 mmol) were added to the glass tube as monomers, CuI (200 mg) and Pd (0) (50 mg) were added as catalysts, and stirred for 20 min in a nitrogen atmosphere. The reactants were reacted at 80 °C in the dark for 48 h. After the reaction, the product was allowed to cool naturally. After the crude product was washed several times with chloroform, deionized water, acetone and methanol, the obtained product was extracted with a methanol solution by Soxhlet extraction until the solution was clear. The product was dried in a dryer at 80 °C for 12 h to obtain a solid phase (CMPs-9), and the dried sample was stored at room temperature for later use.

[0052] Adsorption of Radioactive Elements Iodine and Cesium by Mesoporous Hollow CMPs Microspheres

[0053] Test conditions:

[0054] Iodide ion adsorption experiment: The mesoporous hollow CMPs microspheres were first soaked in methanol and then placed in 30 mL of potassium iodide solution with different concentrations (0.02 mmol L -1 , 0.04 mmol L -1 , 0.06 mmol L -1 , 0.08 mmol L -1 and 0.10mmol L -1), shake and mix to obtain a mixed solution of CMPs microspheres and potassium iodide, adsorb at 10-50 °C for 2-12 h, and use an ultraviolet-visible spectrophotometer (UV-VIS) to monitor the absorbance change of the potassium iodide solution containing the adsorbent material under static conditions. Test 3 mL of the clear solution regularly until the absorbance remains constant and is in equilibrium. The change in absorbance can directly reflect the change in iodine ion concentration.

[0055] Cesium ion adsorption experiment: First, the mesoporous hollow CMPs microspheres were soaked in methanol, and then placed in 30 mL of cesium chloride solution of different concentrations (400ppm, 500ppm and 600ppm), and the mixed solution of CMPs microspheres and potassium iodide was obtained after shaking and mixing. The mixed solution was adsorbed at 10-50°C for 2-12 hours, and its concentration was determined by inductively coupled plasma mass spectrometry (ICP-MS). When extracting the liquid to be tested, it is necessary to ensure that the supernatant is clear enough, and the liquid to be tested needs to be filtered through a 0.45 μm syringe.

[0056] The preparation process of the CMPs microspheres with high adsorption, sensitive recognition, strong affinity and good stability of the present invention is as follows: Figure 1 As shown in Figure 2, mesoporous hollow CMPs microspheres were synthesized by Sonagashira-Hagihara coupling condensation reaction. Figure 2 It can also be clearly seen that CMPs-1 and CMPs-2 (Examples 1 and 2) prepared by the present invention are both special hollow structures, and CMPs-1 (Example 1) is a microsphere with a diameter of about 300 nm. This special hollow structure can effectively solve the problem of low diffusion rate caused by low temperature and microporous structure in iodine / cesium ion transfer. In addition, it is shown that the preparation strategy based on quantum sieving effect proposed by the present invention can construct a hollow microsphere structure.

[0057] Figure 3 a and b show that CMPs-1 (Example 1), CMPs-2 (Example 2) and CMPs-3 (Comparative Example 2) are typical amorphous polymers. The vibration peak of the conjugated system of CMPs on the aromatic ring (1700 cm −1 Up to 1300 cm −1 ) and NH and CH stretching vibration peaks (3400 cm −1 ) all exist, proving that the present invention successfully prepared three CMPs materials. Figure 3In order to study the pore structure and pore size distribution of the material, it can be seen from the N2 adsorption-desorption curve that the adsorption isotherms of CMPs-1 (Example 1) and CMPs-2 (Example 2) are type IV isotherms, and have obvious H3 type hysteresis loops, indicating a mesoporous structure. The Barret-Joyner-Halenda (BJH) adsorption pore distribution test analysis shows that the pore size distribution of CMPs-1 (Example 1) and CMPs-2 (Example 2) is mostly 2-50 nm, especially the mesoporosity of CMPs-1 (Example 1) is as high as 94.5% (Table 1). The pore size distribution of CMPs-1 (Example 1) synthesized based on the kinetic quantum sieving effect is mainly concentrated in 3-8 nm. This mesoporous structure is not only beneficial for the transmission of substrate reactants, but also the pore size of the mesopores is more conducive to the exposure of other pores, making the distribution surface of the adsorption active sites larger. Since the long chain of 3,5-dibromo-2-pyridinamine does not match the molecular size of I / Cs, the pore size of the synthesized comparative example 2 (CMPs-3) is almost entirely distributed in the range of 10-50 nm, belonging to large mesoporous materials, and there are few small mesopores that match the molecular size of I / Cs; in addition, the pore size distribution of comparative example 1 (CuOHS) synthesized using sucrose without the kinetic quantum sieving effect is mainly concentrated around 2 nm, belonging to microporous materials, and the pore size structure cannot match the molecular size of I / Cs. Moreover, the synthesized comparative examples 2 (CMPs-3) and comparative example 1 (CuOHS) do not have a special hollow structure.

[0058] These findings collectively indicate that by cleverly designing the molecular chain length, type and unit ratio of the monomers based on the kinetic quantum screening effect, not only can the pore structure of the CMPs adsorption material be precisely regulated to construct a mesoporous structure, but it is also possible to construct CMPs materials with special hollow structures.

[0059]

[0060] Figure 3gkIn order to further explore the mechanism of the formation of hollow and mesoporous structures in CMPs materials, the chemical bonding environment and carrier interaction of the composite materials were first evaluated by X-ray photoelectron spectroscopy (XPS). CMPs-1 (Example 1) showed two peaks (283.9 eV and 284.9 eV) in the binding energy region of carbon, which were attributed to CH and C≡C, respectively. Similarly, the two peaks of CMPs-2 (Example 2) were CC at 284.8 eV and C6H5X at 286.6 eV, respectively. In addition, the scanning of CMPs-1 (Example 1) and CMPs-2 (Example 2) in the bromine binding energy region revealed peaks of CH3-Br and Br3d. The above results jointly prove that the formation of hollow and mesoporous structures in the present invention is formed by designing building monomers with different spatial structures and molecular chain lengths using the Sonogashhara-Hagihara cross-coupling condensation reaction.

[0061] also, Figure 3 iThe thermal stability of the four adsorbent materials under N2 atmosphere was explored by thermogravimetric analyzer (TGA). At the first decomposition temperature (100°C), the loss of CMPs-1 (Example 1), CMPs-2 (Example 2) and CMPs-3 (Comparative Example 2) was less than 1%, while the mass loss of CuOHS (Comparative Example 1) was 4%. Secondly, at the second decomposition temperature, CMPs-1 (Example 1), CMPs-2 (Example 2) and CMPs-3 (Comparative Example 2) began to thermally degrade at 305°C, 300°C and 285°C, while CuOHS (Comparative Example 1) began to decompose at 265°C. This shows that the CMPs material synthesized based on the kinetic quantum sieving effect has excellent thermal stability.

[0062] Figure 4 a is a schematic diagram of the adsorption process of iodine / cesium ions by four adsorbent materials, and the adsorption capacity was measured by UV-VIS and ICP-MS. Figure 4 b is to adsorb CMPs-1 in potassium iodide solution for 30 minutes under static conditions to explore the absorbance changes of the solution during the adsorption process and the characteristic absorption wavelength of iodide ions (225 nm). The standard curve of iodide ion solution concentration and absorbance obtained by the Beer-Lambert law can calculate the mass adsorbed by the adsorbent. Figure 4 cf comparison revealed that the maximum adsorption capacity of CMPs-1 (Example 1), CMPs-2 (Example 2) and CMPs-3 (Comparative Example 2) and CuOHS (Comparative Example 1) was 0.10 mmol L -1 When the temperature reaches the extreme low temperature of 10°C, the initial concentration is 0.10 mmol L -1, CMPs-1 (Example 1), CMPs-2 (Example 2), and CMPs-3 (Comparative Example 2) reached adsorption equilibrium after 6 h, 6 h, and 2 h, respectively, and the maximum adsorption capacity reached 16.93 mg g -1 , 13.71 mg g -1 and 6.87 mg g -1 . However, after 6 h of adsorption time, CuOHS (Comparative Example 1) still did not reach equilibrium, indicating that the adsorption rate of CuOHS (Comparative Example 1) was much lower than that of other CMPs adsorption materials. In addition, although CMPs-3 (Comparative Example 2) had a faster adsorption rate, CMPs-1 (Example 1) had the largest adsorption capacity. This is mainly due to the fact that compared with the mesoporous structure of CMPs-1 (Example 1), the mesoporous structure of CMPs-3 (Comparative Example 2) was mainly concentrated in a larger mesopore range (10-50 nm), which led to the leakage of target molecules during the adsorption process. Most importantly, compared with CMPs-3 (Comparative Example 2) and CuOHS (Comparative Example 1), CMPs-1 (Example 1) with a hollow mesoporous structure had the most significant iodine adsorption capacity (16.93 mg g-1). In addition, the pore size distribution of CMPs-1 (Example 1) was concentrated in the range of 3-8 nm ( Figure 3 c, d), indicating that it has the most suitable pore size for a good adsorption channel. In addition, the iodine adsorption performance, synthesis method and synthesis temperature of CMPs-1 (Example 1) synthesized in the present invention with matching pore size at extremely low temperature are better than those reported in other literatures (Table 2). Figure 4 g is to further explore the cesium adsorption performance of the prepared material. At 600 ppm, the maximum adsorption capacity of CMPs-1 (Example 1) for cesium ions is 2.50 mg g -1 The absorption of cesium ions reached equilibrium several times within 90 min. The maximum adsorption capacity of CMPs-2 (Example 2) for cesium ions at 600 ppm was 4.75 mg g -1 , the adsorption equilibrium time is only 10 minutes. According to the above analysis, since the pore size of CMPs-2 (Example 2) is more distributed between 2-5 nm than that of CMPs-1 (Example 1), it is conducive to the diffusion of cesium ions. Therefore, CMPs-1 (Example 1) has better selectivity for iodine ions, while CMPs-2 (Example 2) has a faster adsorption rate and a larger adsorption capacity for cesium ions.

[0063]

[0064] Figure 5The purpose is to further explore the adsorption kinetics and adsorption mechanism. First, the adsorption kinetics model was determined by fitting the adsorption data at different times using the pseudo-first-order kinetic model, pseudo-second-order kinetic model, and intraparticle diffusion model. 2 =0.9921), CMPs-2 (Example 2) (R 2 =0.9727) and CMPs-3 (Comparative Example 2) (R 2 =0.9750) are closer to 1 than the coefficients of the pseudo-first-order kinetic model (0.9267, 0.9248, 0.9398). Figure 5 ad and Table 3). CuOHS (Comparative Example 1) is more consistent with the pseudo-first-order kinetic model (R 2 =0.747>0.9623). This indicates that CMPs-1 (Example 1), CMPs-2 (Example 2) and CMPs-3 (Comparative Example 2) are more consistent with pseudo-second-order kinetics, indicating that the rate-limiting step of adsorption is chemical adsorption. Figure 6 ad is to use the intraparticle diffusion model to explore the diffusion behavior and determine the rate-limiting step that controls the adsorption process. The intraparticle diffusion fitting curves of the four adsorbent materials all show the characteristics of C≠0 (for example, the C of the three linear graph fitting curves of CMPs-1 (Example 1) are 5.91, 8.55 and 16.37, respectively), indicating that intraparticle diffusion is not the only controlling step of adsorption. In addition, the diffusion parameter k P1 >k P2 >k P3 (For example, k of CMPs-1 (Example 1) P1 , k P2 and k P 3 are 2.82, 1.71 and 0.78 respectively), indicating that the adsorption sites on the adsorbent are occupied by the adsorbent, resulting in a decrease in the adsorption rate and eventually reaching equilibrium. The C of CMPs-2 (Example 2) also satisfies C≠0 (2.8038, 4.7028 and 8.3181), and its k P Also gradually decreases (k P1 =3.8601>k P2 =2.7271>k P3 =1.1275). The first stage of the intraparticle diffusion model represents surface diffusion, the second stage represents mesopore diffusion, and the third stage represents micropore diffusion. The above results are consistent with the design concept of this patent using the kinetic quantum sieve (KQS) of the material pore size for adsorption. Figure 6el shows that the correlation of the Freundlich isotherm model of the three CMPs materials (0.9752, 0.7278 and 0.8969) is greater than the correlation of the Langmuir isotherm model (0.9575, 0.6809 and 0.8056), while the Langmuir isotherm model of CuOHS has a greater correlation. These results confirm that the adsorption of the three CMPs materials applied to the Freundlich isotherm model is multilayer adsorption, which is consistent with the above results of intraparticle molecular diffusion. CuOHS is more in line with the Langmuir model, and the adsorption mechanism is monolayer adsorption. Figure 7 is an adsorption mechanism diagram. The above results collectively indicate that the adsorption process of iodine-cesium ions by CMPs-1 (Example 1) is multi-molecular layer chemical adsorption. The pore size and π-conjugated network structure matched by the CMPs material are conducive to molecular diffusion, which can accelerate the adsorption rate and provide a more suitable and stable environment for the adsorption process. The kinetic quantum sieve (KQS) of the pore size plays an important role in the chemical adsorption of iodide ions by CMPs-1 (Example 1). In addition, the spherical hollow structure can effectively amplify the diffusion rate and promote the material's recognition of guest molecules. The more active sites exposed by the hollow structure, the more binding sites can be provided for the adsorbed ions, enhancing the adsorption performance and improving the adsorption efficiency of iodine / cesium ions.

[0065] Figure 8 a and b demonstrate the acid-base stability of the product. Even under the harsh condition of pH = 13, the adsorption performance of CMPs-1 (Example 1) for iodide ions (5.92 mg g -1 ) is only slightly higher than the initial value (15.93 mg g -1 ) decreased by about 30%. In particular, the adsorption capacity of CMPs-2 (Example 2) at pH = 3 can reach 20.42 mg g -1 , which is 1.2 times that at pH = 7. The results show that CMPs-1 (Example 1) and CMPs-2 (Example 2) have excellent acid and alkali resistance. Figure 8 c proves the high temperature stability of the product. At 30 °C, the maximum iodine adsorption of CMPs-1 (Example 1) is 26.32 mg g -1 , is at 10℃ (16.93 mg g -1 ). In addition, the maximum adsorption capacity of CMPs-2 (Example 2) at 50 °C was 21.12 mg g -1, which is 1.5 times higher than that at 10°C. CMPs-3 (Comparative Example 2) at 50°C increased by 2.6 times compared to 10°C. However, the optimal adsorption amount of CuOHS (Comparative Example 1) appeared at 20°C, after which the adsorption amount began to decrease with increasing temperature. This shows that the CMPs material constructed by this patent has good thermal stability and can exhibit excellent adsorption performance in a wider temperature range. Figure 8 d proves the cyclic stability of this product. After four cycles, CMPs-1, CMPs-2, CMPs-3 and CuOHS decreased by 0.5 times, 0.6 times, 0.2 times and 0.7 times respectively. The main reason for the decrease in adsorption is the blockage of the pores in the material by the target molecules, but the adsorption material constructed by this patent can be further recycled by analysis. The above results show that the hollow mesoporous CMPs microspheres constructed based on the kinetic quantum sieving effect have excellent iodine / cesium adsorption performance and stability.

[0066]

[0067] In summary, the present invention is based on the kinetic quantum sieving (KQS) effect. By cleverly designing 2,6-dibromonaphthalene, 2,7-dibromonaphthalene and 1,3,5-triethynylbenzene with different spatial structures as building blocks, the Sonogashhara-Hagihara cross-coupling condensation reaction is used to synthesize CMPs microspheres with matching pore sizes and special hollow structures. Based on the special hollow structure of the synthesized CMPs material, the problem of low diffusion rate caused by low temperature and microporous structure in I / Cs ion transfer can be effectively solved. Compared with the adsorption values ​​of other literature at 30°C, the CMPs-1 prepared by the present invention showed a high adsorption rate of iodide ions of up to 16.93 mg g in a static adsorption experiment at an extreme low temperature of 10°C within 6 hours. -1 The adsorption capacity of the existing materials is not effective at the extreme low temperature of 10 ° C, let alone such excellent adsorption capacity. The adsorption rate fitted by the pseudo-second-order kinetic model is 0.11 g mg -1 h -1 In particular, CMPs-1 exhibited excellent iodine adsorption performance at 30 °C (26.32 mg g -1 ), which is 1.6 times the adsorption amount at 10 °C. This is mainly attributed to the matching mesoporous structure (3-8 nm) of the synthesized CMPs material and the three-dimensional network that can provide sufficient space to accelerate the diffusion rate of reactants and intermediates and expose more active sites. Due to the inherent π-π conjugated structure of the CMPs material, CMPs-1 maintains its excellent alkali resistance and maintains effective iodide ion adsorption capacity (16.93-5.92 mg g) in a wide pH range (7-13). -1). More importantly, our work provides an ingenious design idea to construct an adsorbent material with high adsorption, sensitive recognition, strong affinity and good stability. Therefore, the synthetic strategy provided by the present invention can provide inspiration for the design and construction of porous functionalized adsorbent materials for efficient adsorption / separation of specific targets.

[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Application of mesoporous hollow CMPs microspheres based on kinetic quantum sieving effect in the adsorption of radioactive elements in solution, characterized in that: The radioactive element is iodine or cesium. The preparation method of the mesoporous hollow CMPs microspheres includes: using 1,3,5-triethynylbenzene and a brominated compound as monomers, CuI and Pd as catalysts, adding them into a mixed solution of triethylamine and toluene, reacting them in a nitrogen atmosphere at 60-90° C. in the dark for 40-50 hours, cooling naturally after the reaction, washing, performing Soxhlet extraction with a methanol solution, and then drying to obtain the mesoporous hollow CMPs microspheres; the brominated compound is 2,6-dibromonaphthalene or 2,7-dibromonaphthalene; and the molar ratio of 1,3,5-triethynylbenzene to the brominated compound is 1:

1.

2. The use according to claim 1, characterized in that: The mass ratio of the 1,3,5-triethynylbenzene to CuI is 1:5-1:30; the mass ratio of CuI to Pd is 1:1-4:

1.

3. The use according to claim 1, characterized in that: In the triethylamine and toluene mixed solution, the volume ratio of triethylamine to toluene is 1:0.5-1:

2.

4. The use according to claim 1, characterized in that: The drying temperature is 60-90°C and the drying time is 10-15 hours.